Determination of the Parameters Controlling Mixed Convection in Double Lid Driven Shallow Rectangular Cavity Uniformly Heated - Louaraychi, A.; Lamsaadi, M.; El Harfi, H.; Kaddiri, M.; NaÃ¯mi, M. (International Journal of Engineering and Technology, 2018)
Mixed convection, in double-lid driven horizontal rectangular cavity filled with a Newtonian fluid and subjected to uniform heat flux along the vertical walls, has been studied numerically, via the finite volume method, and analytically, by using the parallel flow concept. A good agreement has been found between the results of the two approaches. The frontiers of transition from one regime to another of convection (forced-mixed and mixed-natural) were determined by a modified Richardson Number. Moreover, it has been found that the parameter which specifies the natural and the forced convection regime is Gr/Re3.Â